2013
DOI: 10.4012/dmj.2013-032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different adherend materials and combinations on in vitro shear bond strength

Abstract: The influence of different adherend and substrate materials on shear bond strength (SBS) test was estimated. Ceramic plates (IPS e.max press) were cut, polished, abraded, and applied with two resin cements (Panavia F/Biscem). The SBS values of 30 groups were measured. The groups consisted of five combinations of adherend and substrate materials for each adhesive system and three different bonded areas (2, 4, and 6 mm diameter) for each combination. The failure modes were examined using a stereomicroscope. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The adhesion of resin composite to ceramic vs. resin composite showed a significant difference for the test methods SBT and µTBT. These findings are consistent with one other study (SBT) in which different substrate materials showed a significant effect on the SBS [ 29 ]. µTBT showed the most indicative outcomes for composite adhesion to both composite and ceramic, and associated failure mode.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The adhesion of resin composite to ceramic vs. resin composite showed a significant difference for the test methods SBT and µTBT. These findings are consistent with one other study (SBT) in which different substrate materials showed a significant effect on the SBS [ 29 ]. µTBT showed the most indicative outcomes for composite adhesion to both composite and ceramic, and associated failure mode.…”
Section: Discussionsupporting
confidence: 93%
“…Bonding of glass ceramics to resin composite showed for µSBT (6.6 ± 1 MPa) B the lowest and µTBT (24.8 ± 7 MPa) C,D the highest test values (SBT (14.6 ± 5 MPa) A,D and in between TBT (19.9 ± 5 MPa) A,B ) ( p < 0.05). Shear bond strength, when alternating adherent and substrate of glass ceramic and composite, was shown to be affected by the type of adherent-substrates assembly [ 29 ] and by the size of bonded area. Previous studies have demonstrated that the bonded area and bond strength are adversely correlated, which is not the case in our study, where SBT is higher than microSBT for both [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations